The Effect of Clenbuterol on Growth Performance of Growing Male Pig - Wayan Sukarya Dilaga (International Journal of Science and Engineering, 2012)
This research was aimed to determine the response of growth performance of growing male pig fed various levels of clenbuterol. The experiment was conducted using 2 x 3 factorial completely randomized design 4 times repetition. The first factor is the type of pig (L = K = local pigs and imported pig, while the second factor is the level of clenbuterol (T0 = 0 mg / kg of feed; T1 = 0.20 mh / kg of feed and T2 = 0.40 mg / kg of feed). The were 24 male grower pigs consist of 12 local pigs and 12 imported pigs with initial body weight 28.27 kg ± 52.5. Pigs kept in individual cages for 6 weeks which is 2-week adaptation period and 4 weeks for data retrieval, with the same kind of feed consist of 27.8% bran, 55.5% and 16.7% corn concentrate. Pigs are feed 2 times a day based on their growth phase. Water was provided by ad libitum method. Variables measured were body weight gain, feed intake and feed conversion. The data obtained were analysed by range test followed by orthogonal polynomials. The results shows that clenbuterol were able to increase body weight gain, decreasing feed consumption and feed conversion. Local pig show a higher feed intake and body weight gain than imported pig, but lower feed conversion than imported pig. Statistical analysis showed no real difference for all variables. Keywords— clenbuterol, body weight gain, feed consumption, feed conversion